Experiences of medical educational managers in the early COVID-19 pandemic: A qualitative thematic analysis - Masoomeh Imanipour; Seyede Fatemeh Gheiasi; Leila Taheri (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: The coronavirus (COVID-19) pandemic changed and disrupted education at medical universities. Educational managers face new challenges and special complexities to manage this situation. This study aimed to explain the experiences of educational managers of Iranian medical universities in the early COVID-19 pandemic. MATERIALS AND METHODS: This descriptive-qualitative study was conducted at the Tehran University of Medical Sciences, 2020-2021. The study population included all educational managers in one of the positions of the dean of the faculty, educational Vice-Chancellor, head of the department, and other relevant educational directors in medical sciences universities during the COVID-19 pandemic. Data collected from semi-structured interviews were analyzed in MAXQDA2020 software using the thematic analysis approach. RESULTS: Four main themes and nine subthemes were identified: "The ups and downs of the transition from face-to-face training to virtual training," "Crisis in educational management," "Testing and Evaluation: Obstacles and Problems," "Education and lessons learned from COVID-19." CONCLUSION: Themes identified from the experiences of educational managers provide new information about the negative and positive effects of the COVID-19 pandemic on the learning and teaching process of medical sciences students. Lessons learned and experiences of educational managers in medical sciences universities amid the COVID-19 pandemic will help health education policymakers so that they can create transformation and innovation in the education of medical science students. Strengthening the e-learning infrastructure will help to create a foundation for a rich way of educating medical students in the post-corona era and when the outbreak of other emerging diseases is inevitable in the future.